Foundations of national identity : from Catalonia to Europe - Llobera, Josep R. (New directions in anthropology, 2004)
"Since its emergence in the 19th century in response to feudalism, nationalism has been a mixed blessing. Originally seen as a positive force, often enough it has resulted in warfare and persecution of minorities, so much so that, over time, it has been considered a social evil whose apparent decline has been greeted as a positive development. The author disputes this or rather, he maintains that the picture that emerges is more complex: nationalism is not disappearing but has taken on a different form.